Role of Vitamin E in the Treatment of Primary Dysmenorrhea - Imrana Rasheed, Shakeela Rasheed, Asma Qamar Mudassar, Neelam Saba, Iqra Javaid, Irum Saba, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Primary dysmenorrhea is the common gynecologic problems, particularly among adolescent girls. The pain is severe during the first and/or second day of bleeding & usually lasts up to 72 hours. More than 55 to 80% of post-menarche women are thought to experience primary dysmenorrhea. Both vitamin E and a placebo may lessen dysmenorrhea-related pelvic pain, although vitamin E appears to do more significantly Objective: To find the role of vitamin E in the treatment of Primary dysmenorrhea Methodology: This randomized placebo-controlled trial was conducted at JankiDevi Jamiat Singh Maternity Hospital Lahore and Sir Syed Hospital Karachi from 1stJune 2021 to 31stMay 2022. Sample size 70 with age 16-28 years with unmarried women; regular menstrual cycles; no urogenital disorders; no previous history of abdominal or pelvic surgery. To check severity of pain we used Visual Analog Scale (VAS) & Cox Menstrual Symptom Scale (CMSS) was used for grading the pain duration. Pain duration was categorized as follows: score 1: ≤0-0.5 hours of pain; score 2: 0.5-1 hours of pain; score 3:>1 hour of pain; score 4: >1 day of pain. Two groups were formed from the sample. Vitamin E 400 units/day in two divided doses was prescribed for the first group to begin the treatment course (5 days in a month,), and Placebo was given to the second. Data was entered and analyzed in SPSS. Result: Total 70 were enrolled. There were 35 women given Vitamin E and 35 were given placebo. In Group 1, the mean age was 21.57+ 3.35 and in Group 2, the mean age was 22.0+3.05.Before treatment, the mean of VAS pain score was 49.29 in Vitamin E group ad placebo group was 58.71mm and after treatment, the mean of Vas pain score was reduce to 34.60 in vitamin E group and placebo group was 44.48. A significant difference was found the severity of pain and duration between the pre- and post treatment in both groups. Table: 2,3 As the comparison indicates, no significant differences were found regarding severity of pain and duration between the groups. ( p < 0.05). This study will help the practioners,gynecologist for in the treatement of primary dysmenorrheal further this will also open the doors for further researches in this field. Conclusion: Vitamin E helps to relieve pain in primary dysmenorrhea. It can be considered as a universal medicine in the treatment of primary dysmenorrhea since it is a very simple way for pain control with fewer side effects and is cost-effective. Keywords: Dysmenorrhoea, Vitamin-E, nausea, vomiting, gastrointestinal symptoms